Mediation Effects of Fraud Prevention on the Relationship of Internal Control, Risk Management and Organizational Performance - Tuti Dharmawati; Safaruddin; Irsyad Kamal; Pandu Adi Cakranegara; Muhammad Aqshel Revinzky (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2022)
This study aims to determine the effect of internal control and risk management on organizational performance through fraud prevention. This quantitative research type uses descriptive analysis methods and inferential statistics, namely Structural Equation Modeling (SEM) using Partial Least Square (PLS) and Microsoft Excel software. The population in this study were all auditors who worked at the Inspectorate of Southeast Sulawesi Province, amounting to 37 apparatus. By taking a sample using a saturated piece, the number of samples is 37 Apparatus at the Inspectorate of Southeast Sulawesi Province. This research is sourced from primary data and secondary data. Primary data is obtained from the results of questionnaires distributed to each respondent; secondary data is data that has been collected or data obtained from previous research results—analysis of the Structural Equation Model (SEM) using the PLS program. The study's results found that internal control and risk management had a positive and significant effect on fraud prevention; fraud prevention has a positive and significant impact on organizational performance; internal control and risk management have a positive and significant impact on organizational performance through fraud prevention. Although the internal control implemented is reasonable, it needs to be improved by increasing the identification of every possible risk to avoid risks that will occur in the future. We suggest that the Southeast Sulawesi Provincial Inspectorate can review the performance of each division in carrying out operational activities based on the achievement of performance indicators. Improve regular system maintenance activities, thereby minimizing system disturbances—more follow-up on recommendations on audit findings.